Integrating Green Economy with Social Values in Batudulang Coffee Farmers, Sumbawa, Indonesia - Anshori, Syukron; Supriadi, Dedi (UPT Publikasi Ilmiah Unisba, 2024)
This article investigates how to integrate a green economy with social values and political engagement among Batudulang coffee farmers. The goal is to promote sustainable economic development while preserving natural resources and local culture. The village faces challenges in balancing modernization with traditional practices. While social values are strong, natural resource conservation is hindered by rapid development. To address these issues, this study uses a participatory action research approach, involving farmers in every stage. Data is collected through observation, interviews, and discussions. The findings highlight the potential of integrating local knowledge and sustainable practices to improve economic well-being while protecting the environment and cultural heritage. Community participation in ecosystem conservation is crucial, but requires stronger leadership and communication.